An Institutional Repository (IR) with Local Content (LC) at the Redeemer’s University: Benefits and Challenges - Adebayo, Emmanuel 'Layi (My University, 2010)
The paper discusses extensively the benefits and challenges of creating an institutional repository (IR) with local content (LC). The similarity of this to the National Library of Nigeria Legal Deposit (LD) Law was examined. Some of the challenges highlighted include sourcing for materials, cooperation of faculty members, finance, stocking, staffing and use. Despite all these challenges, many benefits can be derived if one faces the challenges squarely.
Keywords: ICADLA, conference, digital library, archive, Nigeria, Ogun, Redeemer's University, Mowe